Resveratrol/Hydrazone Hybrids: Synthesis and Chemopreventive Activity against Colorectal Cancer Cells (2022)
ABSTRACT: A series of resveratrol/hydrazone hybrids were obtained and elucidated by spectroscopic analysis. All compounds were evaluated against colorectal cancer cells (SW480 and Sw620) and nonmalignant cell lines (HaCaT and CHO-K1) to establish the selectivity index. Among the hybrids evaluated, compounds 6e and 7 displayed the highest cytotoxic activity with IC50 values of = 6.5 ± 1.9 µM and 19.0 ± 1.4 µM, respectively, on SW480 cells. In addition, hybrid 7 also exhibited activity on SW620 cells with an IC50 value of 38.41 ± 3.3 µM. Both compounds were even more toxic against these malignant cells in comparison to the nonmalignant ones, as evidenced by higher selectivity indices 48 h after treatment. These compounds displayed better activity and selectivity than parental compounds (PIH and Resveratrol) and the reference drug (5-FU). In addition, it was observed that both compounds caused antiproliferative activity probably exerted by cell cycle arrest at the G2/M or G0/G1 phases, with the formation of cells in the subG0/G1 phase. Furthermore, it was noticed that compound 7 induced mitochondrial depolarization in SW480 cells and positive staining for propidium iodide in both cancer cell lines, suggesting cell membrane damage involving either apoptosis or other processes of death.